Unveiling current and future trends in customer banking experience research: A bibliometric analysis - Yang, Mengxi; Wider, Walton; Xiao, Shuoran; Jiang, Leilei; Muhammad Ashraf, Fauzi; Lee, Alex (Emerald Group Publishing Limited, 2024)
Purpose: This research is the first to use bibliometric analysis to provide insight into the landscape and forecast the future of customer experience research in the banking sector. Design/methodology/approach: We used bibliographic coupling and co-word analysis to delineate the existing knowledge structure after reviewing 338 articles from the Web of Science database. Findings: The bibliographic coupling analysis revealed five key clusters: customer engagement and experience in digital banking; customer experience and service management; customer experience and market resilience; digital transformation and customer experience; and digital technology and customer experience—each representing a significant strand of current research. In addition, the co-word analysis revealed four emerging themes: customer experience through AI and blockchain, digital evolution in banking, experience-driven ecosystems for customer satisfaction, and trust-based holistic banking experience. Practical implications: These findings not only sketch an overview of the current research domain but also hint at emerging areas ideal for scholarly investigation. While highlighting the industry’s rapid adaptation to technological advances, this study calls for more integrative research to unravel the complexities of customer experience in the evolving digital banking ecosystem. Originality/value: This review presents a novel state-of-the-art analysis of customer banking experience research by employing a science mapping via bibliometric analysis to unveil the knowledge and temporal structure.